2011
DOI: 10.1063/1.3601861
|View full text |Cite
|
Sign up to set email alerts
|

Shape transformation of nanoporous GaN by annealing: From buried cavities to nanomembranes

Abstract: Gallium nitride is considered a chemically inert, ceramic-like semiconductor with no effective etchants available at room temperature. In this letter, we study the shape transformation of nanoporous GaN prepared by an electrochemical process. It is found that the curvature-driven mass transport process at typical growth temperatures is effective in shaping GaN on both the nanoscale and microscale into useful configurations such as buried cavities or semiconductor-on-air structures. This process of “micromachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Annealing was carried out at 1090°C for 10 min, and a thick InGaN layer was then regrown at 770°C. The transformation of the geometry of the NP GaN layers during the high-temperature annealing and regrowth has been reported previously [24,25]. NP GaN is metastable at high temperatures because of the large surface area; this results in the transformation of the geometry of the nanopores via surface atomic diffusion.…”
Section: Resultsmentioning
confidence: 92%
“…Annealing was carried out at 1090°C for 10 min, and a thick InGaN layer was then regrown at 770°C. The transformation of the geometry of the NP GaN layers during the high-temperature annealing and regrowth has been reported previously [24,25]. NP GaN is metastable at high temperatures because of the large surface area; this results in the transformation of the geometry of the nanopores via surface atomic diffusion.…”
Section: Resultsmentioning
confidence: 92%
“…Among other methods of micromachining GaN, one can mention an effective technology for shaping GaN on both the nanoscale and microscale that was recently proposed [30]. This technology is suitable for obtaining buried cavities or semiconductor-on-air structures, including a monocrystalline GaN nanomembrane.…”
Section: Other Technological Methodsmentioning
confidence: 99%
“…The prepared NP GaN samples were loaded into a MOCVD reactor for annealing in a N 2 /NH 3 or H 2 /NH 3 ambient. It was suggested that the shape transformation of NP GaN takes place due to surface and gas phase diffusion driven by the minimization of total surface energy, as well as due to dissociation of GaN and the formation of Ga droplets [30]. A 200-nm-thick nanomembrane was prepared by annealing a GaN layer with a specially designed profile in porosity obtained by using a 2-step EC etching process.…”
Section: Other Technological Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Yerino et al, developed another technique which does not rely on a buried sacrificial layer, by using anodic electrochemical etching with a varying potential bias to form undersurface buried cavities. 10 Subsequent annealing in nitrogen/ammonia causes the cavities to merge together which allows the surface to get exfoliated. Here, we demonstrate a new technique for exfoliating GaN nanomembranes with novel characteristics, namely, the non-radiative cores of their threading dislocations (TDs) being etched away.…”
Section: Introductionmentioning
confidence: 99%